Al-Islam and Muhammadiyah Course and Students’ Philanthropic Character Formation: Mata Kuliah Al-Islam dan Muhammadiyah serta Pembentukan Karakter Filantropis Mahasiswa - Effendie , Abdul Haris; Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Higher education plays a crucial role not only in providing academic knowledge but also in shaping students’ moral and social character. Specific Background: In Muhammadiyah universities, the Al-Islam and Muhammadiyah (AIK) course is a key instrument for instilling Islamic values and social responsibility. Knowledge Gap: Limited studies have examined the specific relationship between AIK understanding and students’ philanthropic attitudes using a quantitative approach. Aim: This study investigates the relationship between students’ AIK knowledge, understanding, and involvement with their philanthropic attitudes. Results: Data from 230 respondents were analyzed using Pearson correlation and multiple linear regression. All AIK indicators showed a positive and significant correlation with philanthropic attitude indicators (r = 0.40–0.50, p < 0.01). Regression results confirmed that AIK knowledge, understanding, and participation significantly predicted students’ philanthropic attitudes (p < 0.05), with involvement in AIK discussions showing the strongest coefficient (β = 0.35). Novelty: The study provides empirical evidence on the contribution of AIK education to character building within Islamic higher education. Implications: Strengthening AIK curricula and interactive learning activities can strategically foster students’ social and philanthropic engagement. Highlights: Strengthens philanthropic attitudes through AIK education Quantitative evidence of positive relationship Curriculum recommendations for character building Keywords: Al-Islam and Muhammadiyah, Philanthropy, Character Building, Higher Education, Regression Analysis